2018
DOI: 10.1016/j.amsu.2018.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Acute Acalculous Cholecystitis due to primary acute Epstein-Barr virus infection treated with laparoscopic cholecystectomy; a case report

Abstract: IntroductionEpstein Barr virus (EBV) is a human herpes virus 4, transmitted through intimate contact between susceptible persons and asymptomatic EBV shedders. It usually presents with fever, pharyngitis and lymphadenopathy. Majority of individuals with primary EBV infection recover uneventfully. Acute Acalculous Cholecystitis (AAC) is usually seen in hospitalized and critically ill patients with major trauma, shock, severe sepsis, total parenteral nutrition and mechanical ventilation.Case presentationWe repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
0
11
1
Order By: Relevance
“…Our analysis did not confirm a predominance of females in the group with cholecystitis as highlighted in previous articles …”
Section: Discussioncontrasting
confidence: 90%
“…Our analysis did not confirm a predominance of females in the group with cholecystitis as highlighted in previous articles …”
Section: Discussioncontrasting
confidence: 90%
“…Another patient who also received corticosteroids improved rapidly [29]. In the second patient who underwent surgery, operation improved her symptoms [33].…”
Section: Resultsmentioning
confidence: 94%
“…Histology findings were not reported [10]. e second patient who underwent surgery was a 25-years-old immunocompromised female [33]. e postoperative course was uncomplicated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These cases recovered conservatively without surgery or corticosteroids [7]. Upon a literature review, at least 12 cases of AAC caused by EBV have been reported since the year 2016 [4,[8][9][10][11][12][13][14][15][16][17][18]. Eight patients were females and four patients were males.…”
Section: Discussionmentioning
confidence: 99%